Engagement of Pulvino-cortical Feedforward and Feedback Pathways in Cognitive Computations - Jaramillo, Jorge; Mejias, Jorge F.; Wang, Xiao-Jing (Neuron (Cambridge, Mass.), 2019)
Computational modeling of brain mechanisms of cognition has largely focused on the cortex, but recent experiments have shown that higher-order nuclei of the thalamus participate in major cognitive functions and are implicated in psychiatric disorders. Here, we show that a pulvino-cortical circuit model, composed of the pulvinar and two cortical areas, captures several physiological and behavioral observations related to the macaque pulvinar. Effective connections between the two cortical areas are gated by the pulvinar, allowing the pulvinar to shift the operation regime of these areas during attentional processing and working memory and resolve conflict in decision making. Furthermore, cortico-pulvinar projections that engage the thalamic reticular nucleus enable the pulvinar to estimate decision confidence. Finally, feedforward and feedback pulvino-cortical pathways participate in frequency-dependent inter-areal interactions that modify the relative hierarchical positions of cortical areas. Overall, our model suggests that the pulvinar provides crucial contextual modulation to cortical computations associated with cognition. •Pulvino-cortical pathways modulate attention, working memory, and decision making•The pulvinar controls the effective connectivity within and across cortical areas•A plastic cortico-TRN-pulvinar circuit can estimate decision confidence•The pulvinar can regulate frequency-dependent and hierarchical cortical interactions Very little is known about the function of the thalamus beyond relaying sensory information to the cortex. Jaramillo et al. present a biologically based model of pulvino-cortical interactions and provide a unified account of the pulvinar’s computational role across cognitive tasks.